2016
DOI: 10.1111/jdv.13768
|View full text |Cite
|
Sign up to set email alerts
|

Phase 3, open‐label, randomized study of the pharmacokinetics, efficacy and safety of ixekizumab following subcutaneous administration using a prefilled syringe or an autoinjector in patients with moderate‐to‐severe plaque psoriasis (UNCOVER‐A)

Abstract: BackgroundThe efficacy of ixekizumab, an anti‐interleukin‐17A (anti‐IL‐17A) monoclonal IgG4 antibody, was demonstrated in moderate‐to‐severe psoriasis patients when administered via prefilled syringe (PFS).ObjectiveTo evaluate the effect of two drug delivery devices on the pharmacokinetics (PK) of ixekizumab as well as efficacy and safety with both devices.MethodsIn the first 12 weeks of an open‐label, phase 3 study, moderate‐to‐severe psoriasis patients were randomized to ixekizumab delivery via PFS or autoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 11 publications
1
18
0
Order By: Relevance
“…The study design and primary results, including safety findings, for the UNCOVER-A trial were reported previously. 16 Briefly, in this randomized, open-label, Phase III study, patients with moderate-to-severe Ps were assigned by a computer-generated random sequence to an injection device (prefilled syringe or autoinjector). Patients received 80 mg ixekizumab as one subcutaneous injection every 2 weeks, following a 160 mg initial dose at week 0 (baseline visit; administered as two 80 mg injections).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study design and primary results, including safety findings, for the UNCOVER-A trial were reported previously. 16 Briefly, in this randomized, open-label, Phase III study, patients with moderate-to-severe Ps were assigned by a computer-generated random sequence to an injection device (prefilled syringe or autoinjector). Patients received 80 mg ixekizumab as one subcutaneous injection every 2 weeks, following a 160 mg initial dose at week 0 (baseline visit; administered as two 80 mg injections).…”
Section: Methodsmentioning
confidence: 99%
“…The primary objective was to evaluate the pharmacokinetics of ixekizumab delivered via autoinjector or prefilled syringe. 16 A secondary objective was to evaluate the patient/caregiver experience with the autoinjector using the subcutaneous administration assessment questionnaire (SQAAQ). The SQAAQ is a novel, 12-item, self-administered questionnaire that assesses ease of use of the device and patient confidence while using the device to administer a subcutaneous injection of drug ( Table 3 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Can the difference in efficacy between the two agents be explained by differences in pharmacokinetics? Table compares the basic pharmacokinetic and dosing characteristics of ixekizumab and secukinumab . Both drugs have similar bioavailability when given subcutaneously.…”
Section: Pharmacokinetic and Dosing Characteristics Of Ixekizumab Andmentioning
confidence: 99%
“…In this open label study, patients were randomized to receive ixekizumab 80 mg every 2 weeks up until week 12 following a 160 mg initial dose at week 0. Primary parameters were Cmax (the maximum concentration) and time to reach Cmax (tmax), the results being ~15 μg/mL and 14.8 μg/mL for the prefilled syringe and the auto-injection devices, respectively, with both devices having a tmax of approximately 4 days 20,24…”
Section: Biological Properties and Pharmacokinetics Of Ixekizumabmentioning
confidence: 99%